Information Security Awareness Analysis of the Threat of Data Leakage in Educational Institutions with the ISO 27001 Framework - Muhammad Rijal, Demas; Assydiqi, Mukhamad Fahmi; Prasetya, Yoel Rensisko; Prasetya Ningsih, Lidya Nurhapsari; Putri Anindra, Nisya Kayla; Pambudi, Pandu Dwi Luhur (Universitas Negeri Surabaya, 2024)
In the rapidly evolving digital era, information security has become a major concern for various organizations, including educational institutions that are facing pressures such as